Degradation of (La0.6Sr0.4)0.95(Co0.2Fe0.8)O3-δ Solid Oxide Fuel Cell Cathodes at the Nanometre Scale and Below - Ni,N; Cooper,SJ; Williams,R; Kemen,N; McComb,DW; Skinner,S (ACS Applied Materials & Interfaces, 2016)
The degradation of intermediate temperature solid oxide fuel cell (ITSOFC) cathodes has been identified as a major issue limiting the development of ITSOFCs as high efficiency energy conversion devices. In this work, the effect of Cr poisoning on (La0.6Sr0.4)0.95(Co0.2Fe0.8)O3-δ (LSCF6428), a particularly promising ITSOFC cathode material, was investigated on symmetrical cells using electrochemical impedance spectroscopy and multi-scale structural/chemical analysis by advanced electron and ion microscopy. The systematic combination of bulk and high-resolution analysis on the same cells allows, for the first time, to directly correlate Cr induced performance degradation with subtle and localized structural/chemical changes of the cathode down to the atomic scale. Up to two orders of magnitude reduction in conductivity, oxygen surface exchange rate and diffusivity were observed in Cr poisoned LSCF6428 samples. These effects are associated with the formation of nanometer size SrCrO4; grain boundary segregation of Cr; enhanced B-site element exsolution (both Fe and Co); and reduction in the Fe valence, the latter two being related to Cr substitution in LSCF. The finding that significant degradation of the cathode happens before obvious microscale change points to new critical SOFC degradation mechanisms effective at the nanometer scale and below.